Supporting LGBTQ+ Students: A Focus Group Study with Junior High School Nurses - Laiti Minna; Pakarinen Anni; Parisod Heidi; Hayter Mark; Sariola Salla; Salanterä Sanna (United States, 2025)
LBGTQ+ students often miss the support and information they need in the school nursing, but little is known about junior high school (JHS) nurses’ work with LGBTQ+ students. 15 JHS nurses were interviewed in focus groups about their perceptions of supporting LGBTQ+ students. Four interconnected themes were identified with inductive thematic analysis: (1) JHS nurses’ professional identity and practice; (2) Recognition of sexual and gender diversity in school; (3) Family acceptance process; and (4) LGBTQ+ students as school nursing clients. JHS nurses self-identified as accepting professionals, but having limited skills, knowledge, and education needed in supporting LGBTQ+ students. Supporting LGBTQ+ students is a complex phenomenon, and to enhance JHS nurses’ competence in providing care for these students, sexual and gender diversity needs to be included in evidence-based nursing information sources, covered in nursing education, and the school needs to be secured as LGBTQ+ safe place.